2012
DOI: 10.1590/s0100-29452012000300016
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização social e tecnológica da produção de uvas para mesa em pequenas propriedades rurais da região de Jales-SP

Abstract: A viticultura é uma atividade relevante para os produtores rurais do Estado de São Paulo, sobretudo aqueles detentores de pequenas áreas. O presente trabalho teve como objetivo caracterizar os principais aspectos sociais e tecnológicos utilizados na produção de uvas para mesa na região de Jales (SP). Os dados foram levantados nos anos de 2009 e 2010, a partir da aplicação de questionários a 19 produtores de uva e do acompanhamento do ciclo de produção de 10 propriedades. Os produtores cultivam pelo menos três … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
19

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 5 publications
1
10
0
19
Order By: Relevance
“…In the 2012 crop, 63 sprays were made and 60 were made with fungicides. Costa et al (2012) obtained a similar result. The authors found 59 sprays with fungicides, for the same region.…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…In the 2012 crop, 63 sprays were made and 60 were made with fungicides. Costa et al (2012) obtained a similar result. The authors found 59 sprays with fungicides, for the same region.…”
Section: Resultssupporting
confidence: 58%
“…Niagara Rosada table grape, and the typical trellis system is pergola, spacing 2.00 m x 2.50 m (2,000 plants/ha) under irrigation. Another feature of the region is two pruning events; one formation pruning (September-December) and a production pruning (February-July) to allow harvesting in the off-season of other table grape producing regions of São Paulo State, between June and November (COSTA et al, 2008;COSTA et al, 2012). In the production pruning, between 20 and 25 productive branches are kept per plant, and two bunches per branch on average, totaling 45 bunches per plant.…”
Section: Resultsmentioning
confidence: 99%
“…Among the 16 grape producers, 68.75% are male and 31.25% are female. During the research, it was observed that 44% are aged between 29 to 38 years old, which shows that viticulture is being developed mostly by workers who are in full activity, as observed by Costa et al (2012). As for education, 50% have higher education, 25% high school and 25% elementary school (Table 2).…”
Section: Winegrower Profilementioning
confidence: 81%
“…It is known that the activity shows great importance in the generation of jobs and income, providing economic conditions for the maintenance of families in small properties throughout the country, according to studies by Zarth et al (2011) in southwestern Paraná, by Anzanello et al (2012) in Rio Grande do Sul and by Costa et al (2012) in the Jales Region, SP.…”
Section: Introductionmentioning
confidence: 99%
“…Apesar disso, em 2012 a produção de uva contribuiu com 9,58% do total do volume das frutas produzidas no país ficando atrás apenas da laranja e da banana (PARANÁ, 2014). O plantio da uva é muitas vezes a única fonte de renda para essas famílias produtoras, que inclusive se utilizam de mão de obra familiar, o que reforça a importância da vitivinicultura no estado de São Paulo (COSTA; TARSITANO; CONCEIÇÃO, 2012;GHILARDI;. Além disso, o plantio de uva promove desenvolvimento econômico e mostra-se economicamente sustentável aos produtores: estima-se que no ano de 2012 o lucro obtido na região de Campinas pela produção da cultivar Niágara Rosada foi superior a R$12.000,00 por hectare (CAPELLO, 2014).…”
Section: A Uva No Brasil E O Panorama Do Cultivo Da Videira No Estadounclassified